Optimization of polytomies: State set and parallel operations - Goloboff, Pablo Augusto (2002)
New algorithms for calculating the most parsimonious state sets for polytomies under Fitch parsimony are described. Because they are based on state set operations, these algorithms can be extended for optimization of several characters in parallel, thus increasing speed by a significant factor. This speed increase may facilitate analysis of molecular data sets, many of which contain hundreds of taxa, thousands of multistate nonadditive characters, and numerous polytomies. © 2002 Elsevier Science (USA).